Courier Services in India: Concerns for Effective Service Delivery - Anvekar, Sandhya (Ushus Journal of Business Management, 2007)
The courier industry in India is like a vital link of communication between persons and corporations meant for individual and industrial benefits. It is an industry worth Rs. 50 billions and is on steady pace of development. More than 2300 courier companies operating in India, it is a challenge for the service provider of courier services to be unique, competent and provide effective service delivery. An insight into the crucial and critical incidents of service failure and strategizing by closing these failures will ensure effective service deliveries by the courier service providers. A trained and skilled front stage personnel, committed delivery boys/runners and efficient distribution networking can enable the courier service operators to provide failure free effective service delivery.